The Transformation of Helaran Jurig Sarengseng into Tourism Performance Art in Pataruman District (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Jurig Sarengseng is a traditional art form originating from Pataruman District and presented in the form of a helaran (a traditional dance). To this day, helaran performances generally take the form of processions that enlive various ceremonies and community celebrations, including the anniversary of Banjar City, the commemoration of independence, and arts and cultural festivals. Through community service activities, efforts are being made to transform the Jurig Sarengseng helaran into a tourist performance packaged for the stage. The goal of this activity is to develop a strategy for packaging traditional arts so that they have educational, attractive, and tourist appeal without losing their local value. This community service was carried out for three months in the Jurig Sarngseng Binangun Arts Groups, consisting of 30 people (dancers and musicians). Implementation methods include identifying cultural potential, choreography training for the performance, arranging music and costumes, and mentoring in the packaging of the performance based on community participation. The results obtained indicate an increase in public understanding of the potential of local arts as a tourism asset, the formation of a more structured performance format, and the growth of a collective spirit of residents in making Jurig Sarengseng an icon of sustainable tourism villages. Statistically, the average score increased from 2.02 (low category) to 4.23 (very high category), indicating that the overall quality of the show's packaging had significantly improved. Thus, the transformation of the Jurig Sarengseng parade is not only an innovation in performing arts but also an effective strategy in developing tourist villages based on local wisdom.